Characterization of ZnO/AlOx/benzene thin-film heterostructures grown through atomic layer deposition/molecular layer deposition. (23rd December 2020) - Krahl, Fabian; Ge, Yanling; Karppinen, Maarit
Abstract: Multilayer thin-film structures are promising for many future high-tech applications. We investigate the structure of polycrystalline ZnO thin films with sub-nanometer amorphous inorganic (AlO x ) and organic (benzene) layers grown by atomic/molecular layer deposition. Small quantities of aluminium are typically introduced in ZnO films for doping, while one of the intended functions of the organic layers is to block thermal conductivity. We apply the AlO x and benzene layers both simultaneously and separately, and investigate the resultant superlattice films with transmission electron microscopy, x-ray reflectivity and x-ray diffraction measurements. The study reveals that both AlO x and benzene form distinct layers in the ZnO matrix even down to one atomic/molecular layer. Furthermore, we demonstrate that despite the clear layering, the ZnO grains can penetrate through thin (below ca. 2 nm) benzene and AlO x layers.